Another Side on Indonesian History of Communism through Leila S. Chudori’s Pulang - Gemilang, Adria Vitalya (Universitas Sanata Dharma, 2015)
At present, 2014, Indonesian people learn to exercise their political right in the biggest people party, which is held every 5 years, the presidential election. Observing the debate, the campaign, and the supporters, one can learn that Indonesia has reached a progress in their political life. The progress is achieved through complex process that only some experienced. Back in the 1960s Indonesia experienced an uprising which caused turmoil of its government. Indonesian learnt two versions of its story, one which was officially broadcasted since 1966 and one which is only stated implicitly through some literary works.Reading Leila S. Chudori’s Pulang, there is another side that Indonesians comprehend about the life of the so called communists by the new order regime. It sees the life of the people who are accused of murder and communism. The depiction is far from judging and framing their political agenda, it shows the reader how their life, as human, affected by the event.Culler (1997) states that literature is the noise of culture as well as its information, and it is a writing which requires readers to be engaged in the problem of meaning. Thus, one can learn the history of a nation through its literary works. Pulang is considered particular in its publication because it needs a 6 year process and its first publication was in 2012, the time when Indonesia has achieved a different level of democracy since 1960.First, this paper discusses how Indonesian history, particularly on its political turmoil in 1965, 1968 and 1998, are read and written by Indonesians. Second, it discusses how the present social context influences the discourse of the novel.Keywords: communism, history, new historicism